Design and Build a Sun Tracking System Using a Fuzzy Logic Controller to Optimize the Output Power of the Solar Cell Module - Hamdani Hamdani; Solly Aryza; Zuraidah Tharo; Siti Anisah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The solar cell module is an electric device that can convert sunlight energy to electric energy directly. Some matters cause solar cell module produceselectric energy unoptimally. One of the problem is position of solar cell module is not vertically coming through the sunlight. This problem is caused by daily earth rotation and yearly earth surrounding the sun. Major Topics of this research are producing a fuzzy logic controlling system so that orientation of solar cell module always follows position of sun periodically. And then comparing power of solar cell module which using controlling system to power of solar cell module which in static orientation. Result of this research, controlling system using fuzzy logic controller is produced, for controlling orientation of solar cell module follows sun position, with error about 4.270, so that power of this solar cell module is higher 10.8% than power of static solar cell module. Average power of static solar cell module is about 2,957 watts, and the energy is about 23,656 watt hour. Else power of dynamic solar cell module is about 3,276 watts, and the energy is about 26,208 watt hour.